2017
DOI: 10.2147/copd.s138435
|View full text |Cite
|
Sign up to set email alerts
|

Risk of community-acquired pneumonia in chronic obstructive pulmonary disease stratified by smoking status: a population-based cohort study in the United Kingdom

Abstract: BackgroundSmoking increases the risk of community-acquired pneumonia (CAP) and is associated with the development of COPD. Until now, it is unclear whether CAP in COPD is due to smoking-related effects, or due to COPD pathophysiology itself.ObjectiveTo evaluate the association between COPD and CAP by smoking status.MethodsIn total, 62,621 COPD and 191,654 control subjects, matched by year of birth, gender and primary care practice, were extracted from the Clinical Practice Research Datalink (2005–2014). Incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
(67 reference statements)
3
17
0
1
Order By: Relevance
“…We would like to thank Shukla et al for their interesting and valuable addition to our study, which showed that the risk of community-acquired pneumonia (CAP) was fourfold increased among patients with COPD, regardless of their smoking status. 1 They first speculate that their observation of expression of adhesion molecules (PAFr) in several bacteria that can cause CAP among COPD patients may explain our findings. Although they observed a significantly increased expression of PAFr among smokers with COPD versus smokers with a normal lung function, PAFr expression was not elevated among COPD patients who were ex-smokers.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…We would like to thank Shukla et al for their interesting and valuable addition to our study, which showed that the risk of community-acquired pneumonia (CAP) was fourfold increased among patients with COPD, regardless of their smoking status. 1 They first speculate that their observation of expression of adhesion molecules (PAFr) in several bacteria that can cause CAP among COPD patients may explain our findings. Although they observed a significantly increased expression of PAFr among smokers with COPD versus smokers with a normal lung function, PAFr expression was not elevated among COPD patients who were ex-smokers.…”
mentioning
confidence: 73%
“…We read with great interest the recent paper by Braeken et al which analyzed the associations between COPD and community-acquired pneumonia (CAP), published in your journal. 1 In this large population-based study, the authors have concluded that the risk of CAP increases fourfold in patients with COPD, independent of smoking status. The authors briefly discuss potential smoking-induced mechanisms leading to increased risk of CAP in COPD, such as host physiological and structural changes, increased bacterial virulence and impaired host immunity.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…An analysis of covariance (ANCOVA) was performed to examine the association between pneumonia and the albumin level. We adjusted for potential confounders, including age (continuous variable) (1,8), consciousness level (continuous variable) (18), tube feeding (no or yes) (5,8), mechanical ventilation (no or yes) (19), and pulmonary disease (no or yes) (7,20,21). These variables were additionally entered into models (Models 1-5) (22).…”
Section: Discussionmentioning
confidence: 99%
“…Asap rokok dapat mengganggu kerja klirens mukosilier, merubah struktur dan mengganggu imun lokal pada saluran napas sehingga memudahkan bakteri untuk masuk ke dalam parenkim paru meningkatkan risiko terjadinya pneumonia komunitas. 22 Indikator perbaikan klinis ≤5 hari didapatkan pada 122 pasien (80,8%) dan 29 pasien (19,2%) >5 hari. Lama perawatan pasien dalam penelitian ini adalah 5 hari sesuai dengan pedoman IDSA/ATS bahwa pasien dengan pneumonia komunitas harus dirawat minimal selama 5 hari dan harus bebas demam selama 48-72 jam.…”
Section: Diskusiunclassified